Modeling and Simulation of VSI Fed Induction Motor Drive in Matlab/Simulink - D. Uma; K. Vijayarekha (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The theory of reference frames and switching functions are effective in analyzing the performance of the induction motor fed from VSI (Voltage Source Inverter). In this work, mathematical model of Adjustable Speed Drive (ASD) is developed by taking synchronous reference frame equations for induction motor, switching function concept for VSI and non-switching concept for diode bridge rectifier.  The developed model is implemented using MATLAB/Simulink as it is an important tool for the validation of the proposed model. The performance of induction motor is analysed for different frequencies. The developed model is tested for the steady state behavior of machine drive. The proposed mathematical model is validated by the simulation results.